Methodological framework in applying Geographic Information System (GIS) for parking spaces data / Siti Nurzafira Mohamad Taufik ... [et al.] - Mohamad Taufik, Siti Nurzafira; Ishak, Siti Zaharah; Mohd Yusoff, Zaharah; Mohd Jaafar, Mohd Nizar; Somenahalli, Sekhar (Universiti Teknologi MARA Press (Penerbit UiTM), 2023)
The primary objective of this study is to explore the potential utility of Geographic Information Systems (GIS) in assessing the distribution and availability of parking spaces within urban areas throughout the day. The research focused on the parking facilities within the Majlis Bandaraya Petaling Jaya region in 2022. The dataset encompassed pertinent details such as the geographical coordinates of each parking location, individual parking capacity, the classification of adjacent roadways, and associated pricing information. This comprehensive parking dataset was sourced from the local municipal authority. The investigation entailed correlating parking occupancy rates with factors like parking fees and the time of day. The identification of accessible parking spots and their respective occupancy rates was facilitated through the utilization of a GIS query builder. The Majlis Bandaraya Petaling Jaya effectively employs a computerized geographic information system to manage, process, analyze, and generate geographical and attribute-related information. This system necessitates software, technological infrastructure, databases, procedural frameworks, and human expertise to efficiently manage the accumulated information. Among the diverse applications of GIS, geospatial data analysis is a pivotal component. The findings of this study revealed two significant outcomes: firstly, the conversion of Google Earth's imagery sensing data into a Geographic Information System format was successfully accomplished; and secondly, GIS demonstrated its viability as a tool for comprehensively studying parking lot occupancy across various levels of analysis. The utilization of distribution or mapping maps notably simplifies the tracking of intricate data sets. Therefore, the formulation of distribution maps for parking lot occupancy proves imperative in addressing traffic congestion and related inconveniences.